Effect of Traditional Chinese Medicine in prevention and treatment of anti-tumor drug induced hand-foot syndrome (中医药防治抗肿瘤药物所致手足综合征效果的Meta分析) - ZHOU Qiaoli (周巧丽); ZHOU Fanhua (周樊华) (中西医结合护理)
Objective To systematically evaluate the clinical efficacy of Traditional Chinese Medicine (TCM) in prevention and treatment of anti-tumor drug-induced hand-foot syndrome (HFS). Methods The randomized controlled trials on the treatment of anti-tumor drug induced HFS by TCM published in PubMed, Cochrane library, CNKI, VIP and Wanfang Database were searched by computer according to the inclusion criteria. Two researcher conducted quality assessment of included studies using Jadad scale, and the included literatures were meta-analyzed by Revman 5. 4. 1 software. Results Totally18 standard RCT studies were included, including 1236 patients, 626 in the treatment group and 610 in the control group. The Jadad scale of included studies ranged from 1and 3. Meta-analysis showed that TCM oral administration［OR=0. 33, 95%CI(0. 18, 0. 61), P＜0. 01］and TCM external application［OR= 0. 28, 95%CI(0. 22, 0. 37), P＜0. 01］were associated with better outcomes in the treatment of anti-tumor drug-induced HFS. The total effective rate of the treatment group was higher than that of the control group in the treatment of anti-tumor drug-induced HFS, with a significant difference［OR=0. 29, 95%CI( 0. 23, 0. 37), P＜0. 01］. Conclusion The TCM treatment can improve the total effective rate in the treatment of anti-tumor drug-induced HFS, and the effect was better than the western medicine treatment and placebo. However, the sample size of the included study was small, and the quality of included literature was poor, which may affect the validity of evidence. (目的 系统评价中医药防治抗肿瘤药物所致手足综合征的疗效。方法 检索 PubMed、The Cochrane Library、中国知网(CNKI) 、维普中文科技期刊数据库(VIP) 、万方数据( Wanfang Data) , 纳入符合标准的随机对照试验(RCTs) 。由两名评价员使用Jadad量表对纳入文献进行文献质量评价, 采用Revman5. 4. 1软件进行Meta分析。结果 共纳入18篇RCTs, 1236例患者, 其中治疗组626例, 对照组610例。所纳入文献的质量评分为1～3分。Meta分析结果显示, 应用中药口服［OR=0. 33, 95%CI(0. 18, 0. 61), P＜0. 01］及中医药外用［OR= 0. 28, 95%CI(0. 22, 0. 37), P＜0. 01］防治抗肿瘤药物所致手足综合征在临床疗效均优于对照组, 差异有统计学意义。总体而言, 中医药［OR=0. 29, 95%CI( 0. 23, 0. 37), P＜0. 01］防治抗肿瘤药物所致手足综合征在临床疗效均优于对照组, 差异有统计学意义。结论 中医药在预防抗肿瘤药物所致手足综合征的发生率优于西医常规治疗和安慰剂治疗。但本研究纳入的文献较少且质量不高, 影响了结果的论证强度。)